Bioinspired self-healing soft electronics - Qi, Miao (2023)
Inspired by nature, various self-healing materials that can recover their physical properties after external damage have been developed. Recently, self-healing materials have been widely used in electronic devices for improving durability and protecting the devices from failure during operation. Moreover, self-healing materials can integrate many other intriguing properties of biological systems, such as stretchability, mechanical toughness, adhesion, and structural coloration, providing additional fascinating experiences. All of these inspirations have attracted extensive research on bioinspired self-healing soft electronics. This review presents a detailed discussion on bioinspired self-healing soft electronics. Firstly, two main healing mechanisms are introduced. Then, four categories of self-healing materials in soft electronics, including insulators, semiconductors, electronic conductors, and ionic conductors, are reviewed, and their functions, working principles, and applications are summarized. Finally, human-inspired self-healing materials and animal-inspired self-healing materials as well as their applications, such as organic field-effect transistors (OFETs), pressure sensors, strain sensors, chemical sensors, triboelectric nanogenerators (TENGs), and soft actuators, are introduced. This cutting-edge and promising field is believed to stimulate more excellent cross-discipline works in material science, flexible electronics, and novel sensors, accelerating the development of applications in human motion monitoring, environmental sensing, information transmission, etc.